Poly(ADP-ribose) binding sites on collagen I fibrils for nucleating intrafibrillar bone mineral - Marco A. Zecca; Heather F. Greer; Karin H. Müller; Melinda J. Duer (Proceedings of the National Academy of Sciences, 2025)
Bone calcification is essential for vertebrate life. The mechanism by which mineral ions are transported into collagen fibrils to induce intrafibrillar mineral formation requires a calcium binding biopolymer that also has highly selective binding to the collagen fibril hole zones where intrafibrillar calcification begins, over other bone extracellular matrix components. Poly(ADP-ribose) (PAR) has been shown to be a candidate biopolymer for this process and we show here that PAR has high affinity, highly conserved binding sites in the collagen type I C-terminal telopeptides. The identification of these PAR–collagen binding sites gives insights into the chemical mechanisms underlying bone calcification and possible mechanisms behind pathologies where there is dysfunctional bone calcification.